The quick recovery of thermal loads by impact spectral functions method - Слесаренко, Анатолий Павлович; Костіков, А. О.; Сафонов, Н. О. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2013)
The new methodology for identification of heat flux and heat transfer coefficient on the boundary of the investigated object of complex shapes in real time from the experimental data is proposed. The technique is based on the use of spectral functions of regional impact and a gradual increase the number of regions into which the investigated area is divided and as a consequence the number of parts that make up the boundary where thermal loads are recovered.